Biomimetic soft fibrous hydrogels for contractile and pharmacologically responsive smooth muscle - Ding, Yonghui (Acta Biomater, 2018)
The ability to assess changes in smooth muscle contractility and pharmacological responsiveness in normal or pathological-relevant vascular tissue environments is critical to enable vascular drug discovery. However, major challenges remain in both capturing the complexity of in vivo vascular remodeling and evaluating cell contractility in complex, tissue-like environments. Herein, we developed a biomimetic fibrous hydrogel with tunable structure, stiffness, and composition to resemble the native vascular tissue environment. This hydrogel platform was further combined with the combinatory protein array technology as well as advanced approaches to measure cell mechanics and contractility, thus permitting evaluation of smooth muscle functions in a variety of tissue-like microenvironments. Our results demonstrated that biomimetic fibrous structure played a dominant role in smooth muscle function, while the presentation of adhesion proteins co-regulated it to various degrees. Specifically, fibre networks enabled cell infiltration and upregulated expression of actomyosin proteins in contrast to flat hydrogels. Remarkably, fibrous structure and physiologically relevant stiffness of hydrogels cooperatively enhanced smooth muscle contractility and pharmacological responses to vasoactive drugs at both the single cell and intact tissue levels. Together, this study is the first to demonstrate alterations of human vascular smooth muscle contractility and pharmacological responsiveness in biomimetic soft, fibrous environments with a cellular array platform. The integrated platform produced here could enable investigations for pathobiology and pharmacological interventions by developing a broad range of patho-physiologically relevant in vitro tissue models.